Survival of hatchery Gulf sturgeon (Acipenser oxyrinchus desotoi Mitchill, 1815) in the Suwannee River, Florida: A 19‐year evaluation. (29th September 2014) - Sulak, K. J.; Randall, M. T.; Clugston, J. P.
Summary An experimental release of 1192 hatchery‐reared, individually PIT tagged, 220 days old (296–337 mm TL) Gulf sturgeon, Acipenser oxyrinchus desotoi, was undertaken in 1992 in the Suwannee River, Florida. The original objectives of the 1992 release experiment were to: (1) evaluate survival rate of cultured Gulf sturgeon in the wild vs survival rate of their wild 1992 cohort counterparts, (2) determine the differential effect of release site within the river upon long‐term survival, and (3) evaluate comparative growth rates of recaptured hatchery vs captured wild 1992 cohort Gulf sturgeon. The present investigation addressed those original objectives, plus an additional fourth objective: (4) evaluation of hatchery fish recapture rate change over the 19‐year experiment. The primary objective was to determine efficacy of potential conservation aquaculture for this species in terms of long‐term survival in the wild. Follow‐up 1993–2011 gill net sampling in freshwater reaches (rkm 4–237) and the estuarine river mouth (rkm −6 to 4) yielded recaptures representing 13.0% of the total released. Mean annual hatchery fish mortality (including emigration) rate estimated for the 19‐year period (1993–2011) was more than twice that for same cohort wild fish. Mark‐recapture survival probability (phi) for hatchery fish, 1993–2011, was substantially lower (0.733) than for their wild counterparts (0.888). Mean annual hatchery fish recapture rate, as a percentage of all 1992 cohort fish recaptures, declined significantly after age‐7, coinciding with age of onset of migration into the open Gulf of Mexico. Hypothesized causal factors may be differentially lower fitness in the marine habitat or permanent outmigration due to natal river imprinting failure. Hatchery fish recapture rates varied significantly for fish from the ten release sites, being highest near the river mouth, and lowest for the furthest upriver sites in the Suwannee River and its Santa Fe River tributary. Hatchery fish also displayed a significantly lower growth rate than their wild counterparts through age 3000 days. Cumulative hatchery fish mortality of 99.87% over 19 years predicts <3 individuals would have survived through 2011. From the results of the 1992 release experiment, hatchery supplementation as a Gulf sturgeon conservation measure does not appear to be an effective option.